CAPITAL STRUCTURE DETERMINANTS IN NIGERIA: EMPIRICAL EVIDENCE AND ANALYSIS - Okoro , Samuel Adewale (International Journal of Allied Research in Economics (IJARE), 2024)
Over recent decades, the role of capital structure has become a crucial focus in corporate finance. Various theories have sought to explain the differences in capital structure among firms, suggesting that the choice of capital structure is influenced by factors that affect the costs and benefits of debt and equity financing. Modigliani and Miller (1958 and 1963) proposed that, in a frictionless environment, capital structure does not impact a firm’s value. However, in a world with taxes, capital structure does affect firm value. Building on their hypothesis, three key theories have emerged: the static trade-off theory, the pecking order theory, and the agency cost theory. These theories provide different perspectives on how firms balance the trade-offs between debt and equity to optimize their capital structure. This paper explores these theories and their implications for understanding variations in capital structure across firms